Analysis of Nutritional Components of Horse Radish Tree Flowers (Moringa oleifera) Wildly Grown in Sindh Province - Saghir Ahmed Sheikh; Benish Nawaz Mirani; Shafi Muhammad Nizamani; Aijaz Hussain Soomro; Aasia Akbar Panhwar (Journal of Basic & Applied Sciences, 2017)
The present research study was aimed at determining the proximate and mineral composition of horse radish tree flowers by utilizing standard methodologies. The mean moisture content in fresh, thermally dehydrated, curry, shade dried and boiled fresh /processed samples of horse radish tree flowers was 80.98, 5.40, 68.07, 5.84 and 86.26%, respectively. The vegetable had the highest pH, carbohydrates, total solids, nitrogen free extracts and calorific values in thermally dried samples and crude fiber, ash and protein values were higher in shade dried samples. Whereas, fat and total fatty acids were found higher in curry samples. There was a significant presence of dietary essential micro-nutrients. It was therefore revealed that horse radish tree flowers(Moringa oleifera) when consumed in curry form could also be a good source of nutrients. The inclusion of horse radish tree flowers into the diet could potentially address some of the challenges, such as health benefits, food security and increase life expectancy in Sindh, Pakistan.